CSR as a vehicle for Innovation - Raask, Elina (2006)
When the first computer came out, the only ones who could use it had to have a degree in mathematics or related studies. Today many telecommunication companies are working with community groups to help to bridge the digital divide between generations and provide equal opportunities for the increasing ageing population to have access to global information space, maintain their social ties with their families across the world and equally participate at the market place. A lot of that is done as a part of their Corporate Social Responsibility (CSR) Programmes. At the same time, innovation is considered as a central word for telecommunication companies that have to conform with enormous speed and pace of the market and could be considered as essential capability to compete.